Improving youth well-being and social integration: the role of leisure in organized public spaces in Kazakhstan - Almagul Utepova; Saltanat Aubakirova; Altynay Kadyraliyeva (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of this study is to investigate the impact of youth participation in organized public spaces on the well-being and social integration of young people in Kazakhstan, with a focus on leisure activities. Through empirical research and analysis, the research aims to elucidate how active engagement in these spaces influences the physical, emotional, and psychological well-being of youth. The study involved 420 students from one of Kazakhstan's universities and divided them into the influence and control groups. The research tools were the Youth Well-Being Scale (YWBS) and the Youth Social Integration Scale (YSIS). The influence group demonstrated a significant increase in well-being and social integration. This result confirms the significant positive effect of interventions based on leisure activities in public spaces. The study offers practical recommendations for improving the well-being and social integration of young people. These findings also contribute to the scientific understanding of the gender specifics in this context. The article emphasizes the importance of organizing public space for positive youth development through leisure due to the identified positive effects.